Chemical Decontamination with N-Acetyl-l-Cysteine–Sodium Hydroxide Improves Recovery of Viable Mycobacterium avium subsp. paratuberculosis Organisms from Cultured Milk - Bradner, L. (American Society for Microbiology, 2013)
Mycobacterium avium subsp. paratuberculosis is shed into the milk and feces of cows with advanced Johne's disease, allowing the transmission of M. avium subsp. paratuberculosis between animals. The objective of this study was to formulate an optimized protocol for the isolation of M. avium subsp. paratuberculosis in milk. The parameters investigated included chemical decontamination with N-acetyl-l-cysteine–sodium hydroxide (NALC-NaOH), alone and in combination with antibiotics (vancomycin, amphotericin B, and nalidixic acid), and the efficacy of solid (Herrold's egg yolk medium [HEY]) and liquid (Bactec 12B and para-JEM) culture media. For each experiment, raw milk samples from a known noninfected cow were inoculated with 10(2) to 10(8) CFU/ml of live M. avium subsp. paratuberculosis organisms. The results indicate that an increased length of exposure to NALC-NaOH from 5 to 30 min and an increased concentration of NaOH from 0.5 to 2.0% did not affect the viability of M. avium subsp. paratuberculosis. Additional treatment of milk samples with the antibiotics following NALC-NaOH treatment decreased the recovery of viable M. avium subsp. paratuberculosis cells more than treatment with NALC-NaOH alone. The Bactec 12B medium was the superior medium of the three evaluated for the isolation of M. avium subsp. paratuberculosis from milk, as it achieved the lowest threshold of detection. The optimal conditions for NALC-NaOH decontamination were determined to be exposure to 1.50% NaOH for 15 min followed by culture in Bactec 12B medium. This study demonstrates that chemical decontamination with NALC-NaOH resulted in a greater recovery of viable M. avium subsp. paratuberculosis cells from milk than from samples treated with hexadecylpyridinium chloride (HPC). Therefore, it is important to optimize milk decontamination protocols to ensure that low concentrations of M. avium subsp. paratuberculosis can be detected.